Analisa Implementasi Sensor Gyroscope Pada Pergerakan Robot Humanoid Berbasis Open CM 9.04 - Refli Erdinal; Feri Candra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Humanoid robot itself is a robot that has human-like characteristics. Starting from the physical structure in general humanoid robots have a head, two hands, two legs, but there are some humanoid robots that are very humanoid such as having a waist to the upper body or even a face. . The purpose of this study is to allow the robot to move steadily and balancedly according to the willingness of the tester. This humanoid robot can perform walking, running, jumping, dancing, and much more. Simple gestures such as walking require alignment between actuators, controllers, and built-in programs or commands. It uses an OpenCM 9.04 controller and Gyroscope sensor as its balancing sensor.  Gyroscope sensor used by MPU-6050 which has an output in the form of angular velocity from the direction of 3 axes that is, the x axis that will later become the angle of phi (right and left), and the y-axis will later become theta angle (top and bottom), and the z axis will later become psi angle (front and back). Gyroscope sensors will be implemented to the legs of humanoid robots so that humanoid robots will maintain their balance in standing and walking later. The robot used is a Bioloid Type-A humanoid robot. The results of this test the robot can move as expected by the author and add value to the test results of the programming process of the OpenCM 9.04 microcontroller. Keywords: OpenCM 9.04, Gyroscope, MPU-6050, Bioloid Type-A humanoid robot.